Exploring the Determinants of Socio-Environmental Sustainability in New Business Initiation - Iwan Harsono; Ardi Azhar Nampira; Restu Auliani; Erba Kalo Manik (West Science Journal Economic and Entrepreneurship, 2025)
This study explores the determinants of social and environmental sustainability in new business initiation in Indonesia using qualitative analysis based on insights from five informants, including entrepreneurs, policymakers, and environmental experts. Four key dimensions—stakeholder engagement, regulatory frameworks, cultural values, and resource availability—emerged as critical to sustainability practices. Findings highlight that effective stakeholder engagement fosters trust and accountability, cultural values such as gotong royong align with sustainability principles, and regulatory frameworks offer guidance but face enforcement challenges. Limited access to financial and technological resources remains a significant barrier. The interplay of these determinants underscores the need for integrated strategies to promote sustainability in Indonesian start-ups. The study contributes to understanding how local context shapes sustainable entrepreneurship and offers actionable insights for policymakers and entrepreneurs.